Behavior of eccentrically loaded double circular steel tubular short columns filled with concrete. (15th December 2019) - Ahmed, Mizan; Liang, Qing Quan; Patel, Vipulkumar Ishvarbhai; Hadi, Muhammad N.S.
Highlights: Experiments on circular CFDST short columns loaded eccentrically are presented. Mathematical model is described that predicts the behavior of CFDST short columns. The model incorporates the concrete confinement provided by inner and outer tubes. The behavior and moment distributions in circular CFDST columns are investigated. The model predicts well the behavior of eccentrically loaded CFDST short columns. Abstract: Circular concrete-filled double steel tubular (CFDST) columns in high-rise building structures possess high ductility and strength performance owing to the concrete confinement exerted by the external and internal circular steel tubes. However, the behavior of circular CFDST short columns that are loaded eccentrically has not been investigated either experimentally or numerically. Particularly, numerical studies on the moment-curvature responses, strength envelopes, confinement effects and moment distributions in circular CFDST beam-columns have not been reported. In this paper, experimental and computational investigations into the structural responses of circular CFDST short columns loaded eccentrically are presented. Nineteen short circular CFDST columns with various parameters under axial and eccentric loads were tested to failure to measure their structural responses. Test results are presented and discussed. A mathematical simulation model underlying the method of fiber analysis is proposed that simulates the axial load-moment-curvature relationships as well as the strength interaction curves of CFDST beam-columns composed of circular sections. The mathematical modeling technique explicitly takes into account the confinement of concrete on the responses of CFDST columns. The computational procedure and solution method are given. The accuracy of the computer simulation model is evaluated by comparing computations against experimental data. The significance of material and geometric properties, concrete confinement and axial load ratio on the responses of moment-curvature and strength envelopes of CFDST columns and the moment distributions in concrete and steel components are investigated. The mathematical model proposed not only simulates well the experimentally observed responses of CFDST columns but also can monitor the moment distributions in the steel and concrete components of such composite columns.